AHP기반 에어백 조립 생산 배치 개선 - 최진영; 최윤규 (한국설비안전학회지, 2020)
The automobile airbag assembly production processes in company A can be characterized as multi-product middle-quantity continuous assembly production. Therefore, production cells were arranged in a grid shape and production processes in a cell were placed in a U shape so that various products were produced in one cell. However, recently it has become an urgent task to make feeding materials, withdrawing finished products, and saving production space efficient. Based on this motivation, in this paper, we propose a new improved assembly production layout by using Analytic Hierarchy Process (AHP) to evaluate layout alternatives. Specifically, we extract four decision criteria, generate three production layout alternatives by brainstorming, and choose the best one by using AHP. The selected layout, with U shape of cells and two parallel lines of processes in a cell, could reduce 77.5% of cell feeder’s moving distance and 59.8% of production space area compared to the current one.
Keywords: Airbag Assembly Production Process; Analytic Hierarchy Process; Cell Feeder’s Moving Distance; Production Space; U shape